Incremental length diffraction coefficients for arbitrary cylindrical scatterers. - Yaghjian, A.D (IEEE Transactions on antennas and propagation)
Convenient expressions are derived for incremental length diffraction coefficients (ILDCs) in terms of the far fields of arbitrary cylindrical canonical scatterers composed of linear electromagnetic material. The derivation of these general expressions for ILDCs is based on a surface-current equivalence theorem that states that the electromagnetic fields outside cylindrical sources can be generated to any degree of accuracy by localized electric and magnetic surface currents that lie in a single plane within the source region. This equivalence theorem is proven with the help of cylindrical wave expansions and the Kottler-Franz formulas. It combines with a general even and odd decomposition of cylindrical electromagnetic fields to allow the use of previous formulas for planar surface current ILDCs in the derivation of the general expressions for ILDCs in terms of cylindrical far fields